CORRELATION OF DISTRIBUTOR EXPECTATIONS WITH PERFORMANCE QUALITY OF THE PHARMACEUTICAL SUPPLY PROCUREMENT SECTION AT DR SAIFUL ANWAR HOSPITAL WITH THE SERVQUAL METHOD AS A STUDY BASIS - Prayoga, I Wayan Eka Putra; Puspitasari, Vicky; Mahardika, Yesika Yuristi; Dewanto, Aryo; Hariyanti, Tita (Journal of Community Health and Preventive Medicine, 2025)
The availability of medical devices in hospitals greatly affects the quality of service, safety, and patient satisfaction. Choosing the right supplier is very important to ensure the sustainability of the company and the quality of service. However, distributors also have high expectations for the quality of performance of the hospital drug procurement section related to health supply services, the high-quality performance carried out by the procurement department will increase distributor satisfaction. This study aims to determine the relationship between distributor expectations and the quality of hospital performance, especially in the Pharmaceutical Supply Procurement Section at Dr Saiful Anwar Hospital (RSSA) by using the SERVQUAL Method as the basis for the study.The population in this study is all distributors of pharmaceutical supplies in collaboration with Dr. Saiful Anwar Hospital in 2023 as many as 103 distributors. The research was conducted in September 2023. This study uses an observational analytical design with a cross-sectional design. The variables used were in the form of independent variables, namely the expectations of RSSA pharmaceutical supply distributors, and dependent variables in the form of the quality of performance of the RSSA pharmaceutical supply section, how to collect data using questionnaires distributed through Google Forms. Each dimension measures service expectations and performance totaling 20 questions on a measurement scale of 1 to 4. The data analysis techniques used were descriptive tests and Spearmen correlation tests. The results of the assessment of distributors' expectations on the quality of the performance of the Pharmaceutical Supply Procurement Section were in the high category (71.39±1.14) and the performance quality of the Pharmaceutical Supply Procurement Section was in the good category (69.23±1.14). The relationship between distributor expectations and the performance of the Pharmaceutical Supply Procurement of Dr. Saiful Anwar Hospital in each dimension of service quality also showed a positive correlation. p=<0.001, r=0.689-0.798). Hospital management, especially the pharmaceutical supply team, should maintain the good relationship that has been established so far by improving the performance and quality of services provided to pharmaceutical distributors.